Solitary fibrous tumor of the seminal vesicle: A case report. Issue 9 (March 2019) - Zhao, Ru; Shan, Yanqi; Zou, Liwei; Zhao, Hong; Zheng, Suisheng
Abstract: Rationale: Solitary fibrous tumor (SFT) is an unusual neoplasm, especially when it originates from the seminal vesicle. Herein, we describe a case of SFT that arises from the seminal vesicle. Patient concerns: A 66-year-old man presented to our hospital complaining of a huge irregular tumor in his pelvis during a health checkup. He was worried that the tumor could be a malignant tumor and hence wanted to undergo further examination and therapy. Diagnosis: An inhomogeneous, mixed soft tissue tumor in the pelvis was found during computed tomography (CT) and magnetic resonance imaging. The tumor showed heterogeneous and delayed enhancement during contrast-enhanced CT. The tumor was diagnosed as a cystadenoma originated from the seminal vesicle due to its imaging features. But the pathological diagnosis was SFT that originated from the seminal vesicle. Interventions: Laparoscopic seminal vesicle tumor resection was performed. Outcomes: There was no evidence of recurrence at the 6-month follow-up. Lessons: SFT in the seminal vesicle is extremely rare. It is very difficult to distinguish SFT in the seminal vesicle from the primary tumors as both have similar imaging features. We describe the tumor with SFT being considered as a differential diagnosis when the tumor is found in the seminal vesicle.